Morphological Description of Drosophila melanogaster Wild Type (Diptera:Drosophilidae), Sepia and Plum Strain - Hotimah, Husnul; Purwatiningsih, Purwatiningsih; Senjarini, Kartika (Jurnal ILMU DASAR, 2017)
Drosophila melanogaster is one of the insects which have a very important role in the development of the genetic science. Drosophila melanogaster have many mutation, recently there are many mutant such as sepia and plum strain. Morgan et al have found 85 strain mutan of Drosophila melanogaster. The purpose of these research was to characterize of morphological from the head, thorax, and abdomen. The result show that the morphological of Drosophilla melanogaster wild type, sepia and plum mutant have many similarities. The difference of them are the eyes color, Drosophila melanogaster wild type has red eye, sepia strain has a dark brown eye and plum has a dark purple eye.